Improved traditional phytomedicines in current use for the clinical treatment of malaria. - Willcox, M (2011)
Phytomedicines and "green pharmacies" are promoted by some NGOs and governments as part of their efforts to control malaria. "Improved traditional medicines" (ITMs) are standardised as regards preparation and dose, although not always according to the concentration of active compounds. A systematic literature search revealed that six such phytomedicines are currently government-approved in at least one country and used on a relatively large scale nationally or internationally: Artemisia annua L. (Asteraceae), Cinchona bark (Rubiaceae), Cryptolepis sanguinolenta (Lindl.) Schltr. (Apocynaceae), "Ayush-64", "Malarial-5" and Cochlospermum planchonii Hook. f. ex Planch. (Bixaceae). One further ITM has been developed and is in the process of being approved: Argemone mexicana decoction. Their development, phytochemistry, pharmacology, and clinical trials are reviewed, as well as priorities for future research.